VILNIUS AS A NON-NOSTALGIC PROJECT. LITHUANIAN PROSE TOWARDS MULTICULTURALISM AND THE METAPHOR OF THE PALIMPSEST CHARACTER OF VILNIUS - Kowerko-Urbańczyk, Marta (Porównania, 2013)
The article is based on recognitions of Tomas Vencova, who positively evaluates Vilnius as a multicultural city and interprets the Lithuanian capitol using the metaphor of palimpsest. Theorists have reported a number of concerns with these conceptions. The article presents an analysis of novels by Ricardas Gavelis and Jurgis Kunčinas created in the late eighties and early nineties of the twentieth century. In their prose both Lithuanian authors distanced themself to the concept of multiculturalism and metaphor of the city as a palimpsest and they tried to rewrite its space using non-nostalgic keys.